2014
DOI: 10.1021/am501665s
|View full text |Cite
|
Sign up to set email alerts
|

Bis(2,2,2-trifluoroethyl) Ether As an Electrolyte Co-solvent for Mitigating Self-Discharge in Lithium–Sulfur Batteries

Abstract: Lithium-sulfur batteries suffer from severe self-discharge because of polysulfide dissolution and side reaction. In this work, a novel electrolyte containing bis(2,2,2-trifluoroethyl) ether (BTFE) was used to mitigate self-discharge of Li-S cells having both low- and high-sulfur-loading sulfur cathodes. This electrolyte meaningfully decreased self-discharge at elevated temperature, though differences in behavior of cells with high- and low-sulfur-loading were also noted. Further investigation showed that this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
132
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(134 citation statements)
references
References 28 publications
1
132
1
Order By: Relevance
“…All the capacity retention and capacity degradation are calculated from the third cycle after achieving stabilized capacity. The achieved cycling ability in Figure 5c,d is much better than that of most previous reports 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 48. Only very recently, Cui and co‐workers51 successfully demonstrated that the TiO 2 /S yolk–shell composites can be cycled over 1000 times with a capacity decay of 0.033% per cycle.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…All the capacity retention and capacity degradation are calculated from the third cycle after achieving stabilized capacity. The achieved cycling ability in Figure 5c,d is much better than that of most previous reports 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 48. Only very recently, Cui and co‐workers51 successfully demonstrated that the TiO 2 /S yolk–shell composites can be cycled over 1000 times with a capacity decay of 0.033% per cycle.…”
Section: Resultscontrasting
confidence: 55%
“…However, the insulating nature of sulfur (S) and its reaction products (i.e., Li 2 S), the large volume expansion from S to Li 2 S, along with the dissolution of lithium polysulfide intermediates (i.e., Li 2 S x , 4 ≤ x ≤ 8) into liquid electrolyte and the consequent shuttling effect between the anode and cathode, makes it generally display poor rate ability, limited cycle life and severe self‐discharge 1, 2, 3, 4, 5, 6, 7. Therefore, a variety of strategies have been pursued to circumvent the sulfur cathode problems, including optimization of organic electrolytes8, 9 and fabrication of sulfur‐conductive polymer composites10, 11 and sulfur–carbon‐based composites 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45. Among these approaches, porous‐carbon/sulfur composites12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 are more attractive because porous carbon can i...…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increased ion mobility and ionic conductivity, electrolytes with toluene additive have higher redox currents 132. Wang and co‐workers133 firstly reported BTFE with LiNO 3 to form significantly enhanced SEI film, which is a great step to obtain stable and non‐flammable electrolyte for LMBs. Hollenkamp and co‐workers discussed the effect of LiNO 3 additive and pyrrolidinium ionic liquid on the SEI in Li‐S cells and verified the participation of C 4 mpyr‐TFSI on the SEI formation on the anode 134…”
Section: Sei Regulationmentioning
confidence: 99%
“…The synergetic functions are the result of (1) lower solubility of LiPS in the fluorinated electrolyte, (2) formation of an SEI layer on the surface of the sulfur/carbon cathode by the fluoroether solvent, 13 and (3) formation of the protective layer on the lithium anode by LiNO 3 and TTE reduction reaction. 13,19,26,27 Long-term self-discharge behavior of the cells with different electrolyte compositions was then evaluated by monitoring the voltage decay during resting. As shown in Figure 4a, the cell containing DOL/DME-1.0 M LiTFSI electrolyte without LiNO 3 additive showed severe shuttling during the 1 st and 2 nd charge.…”
Section: Resultsmentioning
confidence: 99%
“…13,19 Fluoroether-containing electrolytes have been reported by other groups to enhance the performance of the Liion battery due to their unique physical and chemical properties; [20][21][22][23] however, it is our idea to use it as an electrolyte co-solvent/additive for the Li-S battery. In this paper, we report the self-discharge characteristics of Li-S battery with the fluorinated electrolyte containing 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE).…”
mentioning
confidence: 99%